المسائل المتفق عليها في التفسير بين ابن مسعود وابن عباس من خلال زاد المسير في علم التفسير لابن الجوزي "سورة البقرة نموذجا" - تجاني, نورة; بوصبيع صالح, الشيماء (University of Eloued جامعة الوادي, 2020)
"الملخص العنوان: المسائل المتفق عليها في التفسير بين ابن مسعود وابن عباس من خلال زاد المسير في علم التفسير لابن الجوزي ""سورة البقرة نموذجا"" تشتمل هذه المذكرة على مقدمة وثلاث مباحث وخاتمة وفهارس: أمَّا المبحث الأول: تطرقنا فيه إلى ترجمة للصحابيين الجليلين ابن مسعود وابن عباس وللإمام الجليل ابن الجوزي وأمَّا المبحث الثاني: فتطرقنا فيه إلى دراسة وصفية لكتاب ""زاد المسير في علم التفسير"" للإمام ابن الجوزي، اسمه، سبب تأليفه، مخطوطاته، طبعاته. ودراسة تحليلة نقدية حول مسلكه من خلال منهجه، ومصادره وطريقة نقله منها ومكانته العلمية واختياراته في ""سورة البقرة""، ومميزاته والمؤاخذات عليه. وأمّا المبحث الثالث: تطرقنا فيه لدراسة المسائل التي اتفق عليها إمامي التفسير ابن مسعود وابن عباس في التفسير من خلال كتاب ""زاد المسير في علم التفسير"" لابن الجوزي. أمَّا الخاتمة احتوت على أهم النتائج التي توصلنا إليها من خلال بحثنا والتي منها: بعد ترجمة للإمام ابن مسعود أنّه إمتاز بكونه من متقدمي الصحابة إسلاما سادس سته، وأنه من أكثرهم علما وقرآنا ومن ألزمهم للسنة، كان ملازما لنبي صلى الله عليه وسلم لا يكاد يفارقه. كما حظى بمنزلة عالية عند النبي صلى الله عليه وسلم الذي أولاه ثقته. ومن خلال ترجمتنا للصحابي الجليل ابن عباس إمتاز الصحابي الجليل كونه من أصغر الصحابة الذين دخلوا الإسلام، وملازما للنبي صلى الله عليه وسلم نال شرف دعائه، وتفوقه في العلم بالقرآن وتفسيره، كان من أهل بيت النبي صلى الله عليه وسلم . ومن خلال دراستنا لشخصية الإمام ابن الجوزي اتضح لنا، أنه إمام ذو همة عالية، حتى أنه كرّس حياته وماله، في طلب العلم والتنوع في فنون شتّى من العلوم الدينية والدنيوية. ثم ختمنا هذه المذكر"Abstract The Title: The Questions Agreed upon in Tafsir between Ibn Masoud and Ibn Abbas through Zad Al-Masir in the Science of Tafsir by Ibn Al-Jawzi ""Surat Al-Baqarah as an Example"" This memorandum includes an introduction, three sections, a conclusion, and indexes: As for the first topic: we dealt with a translation of the great companions Ibn Masoud and Ibn Abbas and the great Imam Ibn Al-Jawzi As for the second topic, we dealt with a descriptive study of Imam Ibn al-Jawzi’s book “Zaad al-Masir fi al-tafsir,” his name, the reason for its composition, manuscripts and editions. And to study a critical analysis of his behavior through his method, its sources, the method of transmitting it from it, his scientific standing, and his choices in Surat al-Baqarah, its advantages and blame for it. As for the third topic: we dealt with it in order to study the issues agreed upon by the Imams of Tafsir Ibn Masoud and Ibn Abbas in Tafsir through the book “Zaad Al-Masir in the Science of Tafsir” by Ibn Al-Jawzi. As for the conclusion, it contained the most important results that we reached through our research, including: After translating Imam Ibn Masoud, he was distinguished for being one of the forerunners of the Companions, the sixth of six Islam, and that he was among the most knowledgeable, the Qur’an, and who obligated them to the Sunnah. He also held a high position with the Prophet, may God bless him and grant him peace, who placed him in trust. Through our translation of the great companion Ibn Abbas, the great companion was distinguished as one of the youngest companions who entered Islam, and associated with the Prophet, may God’s prayers and peace be upon him, attained the honor of his supplication, and his superiority in knowledge of the Qur’an and its interpretation. He was one of the people of the house of the Prophet, may God bless him and grant him peace. Through our study of the personality of Imam Ibn Al-Jawzi, it became clear to us that he is a highly motivated imam, so that he devoted his life and money to seeking knowledge and diversity in various arts of religious and worldly sciences. Then we concluded this note with technical indexes revealing its contents. Praise be to God who helped us for this." .
مذكرة ماستر تخصص تفسير وعلوم قرآن
Keywords: المسائل المتفق عليها - التفسير بين ابن مسعود وابن عباس - زاد المسير في علم التفسير; The agreed upon issues - interpretation between Ibn Masoud and Ibn Abbas - added Al-Masir in the science of exegesis